Investigation of the Quality of Winter Wheat in a Sulphur Fertilisation Experiment, 2001/2002 - Mars, Éva; Győri, Zoltán (Acta Agraria Debreceniensis, 2003)
We have started a small parcell and a factorial S fertilization experiment with winter wheat in the 2001/2002 cropping year to examine its effect on yield and quality. The scene of experiment was the Latokep Experimental Station of the DE ATC (calcareous chernozeem) in case of small parcell examination and the Agricultural Company of Felsőzsolca (brown forest soil) in case od factorial examination.The protein and gluten content of the grain was investigated with PerCon Inframatic 9001 NIR Analyser, then we have measured these parameters with PerCon 8620 infra appliance. After the milling we measured the following parameters: glutenindex, farinographic parameters (farinographic index, water absorption capacity, dough development time, stability, softening, extension) and valorigraphic index.Based on the results there’s no justified relation between the fertilization and the protein and gluten content. The valorigraphic index of the samples taken from Felsőzsolca factory characteristically increased as a result of the S-fertilization. In the small-parcell experiment the values of the water absorption capacity, the dough development time and the softening parameters from the valorigrphic parameters depended significantly from the mineral treatments. Signifikant quality improvement wasn’t experieced.There was sampling in all of critical phenophase (…). The green plant samples were examined on element content with ICP-OES. These measurements are currently in progress.